Tingkat Partisipasi Masyarakat dalam Pengembangan Wisata Alam di Curug Bidadari - Intan Rachmawati; Riza Firmansyah (Fakultas Pariwisata Universitas Pancasila, 2019)
Community participation is the participation of a person in a social group to take part in the ctivities of his community, outside his own work or profession. This study aims to see the characteristics of society, the level of community participation in the development of nature tourism in Curug Bidadari and the relationship of characteristics and levels of community participation. Methods of data collection conducted by distributing questionnaires, interviews, observation and literature study. The data obtained are then analyzed and presented quantitatively and supported by qualitative data, where the results will be expressed in percentage numbers. Data analysis techniques used in this study is to test the validity, reliability test and use the method of spearman rank analysis. The result of research shows that the characteristics of the society are seen in terms of age dominated by the age of 30-40 years as much as 40%, gender in female domination as much as 52%, education in dominance of high school graduates as much as 34% and work in entrepreneurial dominance by 44%. The level of community participation around Curug Bidadari falls into the moderate category of 85% and the relationship of the community participation variable to the characteristics of society as a whole has a very weak relationship. The development of public participation tourism is still less than the maximum due to lack of public understanding of the importance of participation in tourism development activities.